Exoskeleton technology in nursing practice: assessing effectiveness, usability, and impact on nurses' quality of work life, a narrative review - Alexandre Vallée (BMC, 2024)
Abstract The use of exoskeletons in nursing practice has gained attention as a potential solution to address the physical demands and risks associated with the profession. This narrative review examines the effectiveness, usability, and impact of exoskeleton technology on nurses' quality of work life. The review focuses on the reduction of physical strain and fatigue, improved posture and body mechanics, enhanced patient care, usability and acceptance factors, and the broader impact on work life. The effectiveness of exoskeletons in reducing physical strain and fatigue among nurses is supported by evidence showing decreased muscle activation and reduced forces exerted on the body. The usability and acceptance of exoskeletons are critical considerations, including device comfort and fit, ease of use and integration into workflows, user experience and training, compatibility with the work environment, and user feedback for iterative design improvements. The implementation of exoskeletons has the potential to positively impact nurses' work life by reducing work-related injuries, improving physical well-being, enhancing job satisfaction, and promoting psychological and psychosocial benefits. Additionally, the use of exoskeletons can lead to improved patient care outcomes. Challenges and future directions in the field of exoskeleton technology for nurses include cost and accessibility, adaptability to nursing specialties and tasks, long-term durability and maintenance, integration with personal protective equipment, and ethical considerations. Addressing these challenges and considering future research and development efforts are crucial for the successful integration of exoskeleton technology in nursing practice, ultimately improving nurses' quality of work life and patient care delivery.